The Fundamental Role of Stress Echo in Evaluating Coronary Artery Disease in Specific Patient Populations - Raftopoulos, Leonidas; Aggeli, Constantina; Dimitroglou, Yannis; Kakiouzi, Vasiliki; Tsartsalis, Dimitrios; Patsourakos, Dimitrios; Tsioufis, Costas (Current Vascular Pharmacology, 2022)
Stress echocardiography (SE) was initially used for assessing patients with known or suspected coronary heart disease by detecting and evaluating myocardial ischemia and viability. The implementation of SE has gradually been extended to several cardiovascular diseases beyond coronary artery disease, and SE protocols have been modified and adapted for the detection of coronary artery disease (CAD) or other cardiovascular diseases in specific patient populations. This review attempts to summarize current data concerning SE implementation and clinical value in these specific and diverse populations: patients with an intramural course of a coronary artery, known as a myocardial bridge, chronic severe or end-stage hepatic disease, chronic severe or end-stage kidney disease, cardiac allograft vasculopathy, patients scheduled for solid-organ transplantation and other intermediate and high-risk surgery and, finally, patients treated with anticancer drugs or radiotherapy.
Keywords: cancer therapy